Vaping Epidemic in Pakistan: A Silently Emerging Public Health Concern - Farhan Muhammad Qureshi; Samira Faiz Bari; Syeda Sehrish Zehra (Pakistan Journal of Medicine and Dentistry)
Vaping products (VPs), otherwise known as electronic cigarettes was first manufactured back in 2003 in China followed by its initiation to market in 20071. The VPs devices vaporise a controlled dose nicotine through a heating coil with a liquid chemical reservoir using lithium battery 2. Recently, use of VPs has grown exponentially especially among teenagers and adolescent population thus making it an emerging public health issue of Pakistan. Considering a less harmful tobacco substitute, there has been a massive rise in vaping prevalence not only in traditional smokers but in not or never smokers 3. VPs was initiated and promoted as safe and endorsed as a traditional smoking cessation technique in order to counteract the detrimental effects of smoking, while concurrently act as a mood enhancer and pleasure with a sense of euphoria 4.